Analysis of the ν1+2ν2, ν2+ν3, ν1+ν3 and the 2ν2+ν3 bands of HT16O. (December 2021) - Hermann, Valentin; Kamrad, Marcel; Reinking, Johannes; Schlösser, Magnus; Hase, Frank; Orphal, Johannes
Highlights: High-resolution spectrum of tritiated water species further analysed. Line-by-line analysis of 1303 new lines for HT 16 O. Line positions determined at an accuracy of 10 − 2 cm − 1 up to a few 10 − 4 cm − 1 . Differences to ab-initio line positions of the order of 0.3 cm − 1 . Spectroscopic constants determined in A-reduced Watson Hamiltonian. Graphical abstract: Abstract: We present the ν 1 + 2 ν 2, ν 2 + ν 3, ν 1 + ν 3 and the 2 ν 2 + ν 3 bands of HT 16 O that have been analyzed for the first time using a high-resolution infrared spectrum of tritiated water vapour. The spectrum has been recorded from a custom-built light-pipe cell at room temperature using a Bruker 125HR Fourier-transform spectrometer at a resolution of.0075 cm − 1 . In the range from 4715 to 5300 cm − 1, we report 446 new experimental line positions assigned to the ν 1 + 2 ν 2 and 611 new line positions belonging to the ν 2 + ν 3 band. In the range of 5830 to 6440 cm − 1, 165 new experimental line positions were determined for the ν 1 + ν 3 band and 81 line positions were assigned to the 2 ν 2 + ν 3 band. The analysis reveals a systematic shift of the individual line positions compared to the variationally calculated line positions from the Tomsk database which uses the potential energy surface of Partridge and Schwenke. Furthermore, it is observed that the differences between prediction and experiment are depending on the rotational quantum number K a ′ . For each band, the assigned lines were used to determine the spectroscopic constants in the A-reduced Watson Hamiltonian. With a total of 1303 new line positions for HT 16 O we roughly double the number of experimental line positions for this species.